Learning model in school of vocational studies - Bal, Pervin; Yıldırım, Osman (INT SCIENTIFIC CONFERENCE SGEM, 14, KILMENT OHRIDSKY BLVD, SOFIA, 1797, BULGARIA, 2008)
In this research, it is aimed to determine which individual and environmental characteristics affecting training. Instead of both types of evaluation models, to be proactive, the evaluation of training mentioned in this research is focused on how training affects individuals. To this end, in this thesis the factors affecting to the training effectiveness were examined in regard of trainee perspectives. According to the research results, it is revealed that mostly related to the training effectiveness are respectively: trainer's consideration of employees' learning styles, employees motivation to attend the training, employee's organizational affective commitment and employee's belief that the training will add value to his/her career.
Keywords: Learning Model; Vocational Studies; Training Effectiveness; Öğrenme Modeli; Mesleki Çalışmalar; Eğitim Etkinliği